Equity and accessibility in health? Out-of-pocket expenditures on health care in middle income countries: evidence from Mexico ¿Equidad y accesibilidad en salud? Gasto personal de los usuarios en países de ingresos medios: evidencias desde México - Armando Arredondo; Patricia Nájera (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This study analyzes the results of a cross-sectional survey which set out to determine the costs to patients of searching for and receiving health care in public and private institutions. The information analyzed was obtained from the study population of the Mexican National Health Survey. The dependent variable was the out-of-pocket users' costs and the independent variables were the insurance conditions, type of institution and income. The empirical findings suggest that there is a need for a more detailed analysis of user costs in middle income countries in general, where the health system is based on social security, public assistance and private institutions. This study shows that the out of pocket costs faced by users are inequitable and fall disproportionately upon socially and economically marginalized populations. Se presentan los resultados de un estudio transversal, cuyo principal objetivo fue determinar los costos personales de los usuarios en el proceso de búsqueda, obtención y seguimiento de la atención a la salud en instituciones públicas y privadas del sistema mexicano de salud. La información fue obtenida de la Encuesta Nacional de Salud de México. La variable dependiente se refirió a los costos personales de los usuarios y como variables independientes se definieron la condición de aseguramiento, tipo de institución e ingreso económico. Los resultados sugieren que en países de ingresos medios los costos a los usuarios de servicios de salud requieren de un análisis muy detallado, ya que el sistema de salud esta fragmentado en asistencia pública, seguridad social y asistencia privada. Este estudio muestra evidencias de cómo los costos a los usuarios afectan de manera inequitativa a familias de menor ingreso y de mayor marginación social.